Illegal, Immoral, In-touch with society? An Investigation into Criminal Social Responsibility - Sandars, Jonathan (2007)
This study is an investigation of the idea of Criminal Social Responsibility the idea that criminal organisations, in the same way as corporations, may engage with society in order to accrue organisational benefits. From a thorough literature review encompassing both literature on crime and organised crime in particular, as well as literature on CSR practices and motivations, this paper establishes a motivational model for criminal social responsibility. The idea of criminal social responsibility is then investigated through a case study of the internationally recognised terrorist group Hamas. This case study firstly finds that some of the social practices of Hamas can be considered socially responsible, and secondly tests the motivational model suggested from the literature review. The latter element of the investigation presents some refinements to the model as applied to terrorist organisations.